2020
DOI: 10.3389/fphar.2019.01574
|View full text |Cite
|
Sign up to set email alerts
|

Squid Ink Polysaccharides Protect Human Fibroblast Against Oxidative Stress by Regulating NADPH Oxidase and Connexin43

Abstract: Oxidation injury to skin is one of the main reasons for skin aging. The aim of the present study was to explore the protective effect of squid ink polysaccharides and its mechanism of action against H 2 O 2-induced dermal fibroblast damage. Our results show that squid ink polysaccharides effectively reduce the fibroblast oxidative damage mediated by the upregulation of NADPH oxidase and Connexin43. Concurrently, squid ink polysaccharides decrease the ROS induced up-regulation of MMP1 and MMP9 to decrease MMPme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In contrast, SOD, along with GSH-Px, is an effective ROS scavenger. Increased levels of ROS re ect the ability to resist oxidative damage [41]. In the induced POI model, the expression of oxidative stress products (ROS, T-AOC, and MDA) increased, whereas that of antioxidant products (SOD and GSH-Px) decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SOD, along with GSH-Px, is an effective ROS scavenger. Increased levels of ROS re ect the ability to resist oxidative damage [41]. In the induced POI model, the expression of oxidative stress products (ROS, T-AOC, and MDA) increased, whereas that of antioxidant products (SOD and GSH-Px) decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gu et al [34]found that SIP has the capability to reduce levels of reactive oxygen species (ROS) and malondialdehyde (MDA) content in the testes of male mice, enhance superoxide dismutase (SOD) activity, and protect the normal functioning of mitochondria.. Our team's extracted polysaccharides were found to have similar composition and functionality to those extracted by other researchers. It was also demonstrated that SIP exhibits a strong antioxidant effect and the ability to inhibit H 2 O 2 -induced oxidative stress in normal human skin broblasts [12], which prompted us to explore more deeply whether SIP could play a role in cellular in ammation and realize new applications of SIP in in ammatory dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SOD, along with GSH-Px, is an effective ROS scavenger. Increased levels of ROS reflect the ability to resist oxidative damage [ 41 ]. In the induced POI model, the expression of oxidative stress products (ROS, T-AOC, and MDA) increased, whereas that of antioxidant products (SOD and GSH-Px) decreased.…”
Section: Discussionmentioning
confidence: 99%